Association of Pisouthus tinctorius with Eucalyptus tereticornis in India - Raman, N.; Rajendran, V. (Indian Forester, 1994)
Association of Pisolithus tinctorius with Eucalyptus tereticornis plantations in Vandalur and Kolappakkam (Madras) has been described in this paper.